Clinical manifestations in calotropis poisoning: a prospective study in Government General Hospital Nalgonda, India - Reddy, C. Yadavendra (International Journal of Advances in Medicine, 2019)
Background: Calotropis procera commonly known as Madar is common shrub all over India. Its chemical component Calotropin, which is derived from latex is known to cause injury to eyes and oral mucosa. Toxic manifestations following accidental ingestion are mostly gastrointestinal. This study was aimed at studying the various clinical manifestations of Calotropis poisoning in patients admitted to GGH Nalgonda. Methods: This prospective observational study was done from Feb 2019 to May 2019.All patients both male and female admitted to GGH Nalgonda during this period were studied. Patients below 12 years, pregnant women and patients with earlier gastritis, hepatitis, stomatitis were excluded from the study. The study was carried out in all patients fulfilling the inclusion and exclusion criteria. Results: A total of 60 patients 45 females and 15 males presented during the study period. Most of the patients presented with abdominal pain 15 (25%), hepatitis 10 (16.6%), stomatitis 12 (20%), vomiting 8 (13.3%), diarrhea 6 (10%), hyperkalemia 3 (5%), tachycardia 5 (8.3%), convulsion 1 (1.6%). Conclusions: It was observed from the study that most of the patients had abdominal pain as the major symptom. Stomatitis was the second most common symptom. It was observed consumption of the toxin in lesser quantities produced these symptoms in large quantities produced tachycardia, hyperkalemia and convulsions.